Supplementary Data Table S2 - Hayden Dalton (2022)
This file contains Supplementary Table S2, a table of model inputs which supplement the article “ Geodynamic and isotopic constraints on the genesis of kimberlites, lamproites and related magmas from the Finnish segment of the Karelian craton ”. Submitted to Geochemsitry, Geophysics, Geosystems on 30th December 2021